OPTIMALISASI PERAN KANTOR URUSAN AGAMA DALAM PELAKSANAAN PERJANJIAN PRANIKAH: TINJAUAN FIQH MUNAKAHAT DAN HUKUM POSITIF INDONESIA - Aisyah; Kayla Ramadhini; Shafa Afifah Tasya Kamila; Khairunnisa Dahlan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
A prenuptial agreement is a legal instrument aimed at providing legal certainty and protecting the rights and obligations of prospective spouses in married life. Although it has been regulated under Indonesian law, its implementation remains relatively uncommon. This study aims to analyze the role of the Office of Religious Affairs (KUA) in the implementation of prenuptial agreements from the perspectives of Islamic family law (fiqh munakahat) and Indonesian positive law. This research employs an empirical legal research method with a qualitative approach. Data were collected through interviews, observation, and literature review. The findings indicate that public awareness regarding prenuptial agreements is still low. Based on interviews, only one couple had ever submitted a prenuptial agreement, and the document was submitted only after the marriage had taken place. This demonstrates that the implementation of prenuptial agreements has not yet been optimal. The KUA does not have the authority to draft such agreements but functions primarily in marriage registration and providing legal information. From the perspective of fiqh munakahat, prenuptial agreements are permissible as long as they do not contradict Islamic principles. Indonesian positive law also recognizes prenuptial agreements through Law Number 1 of 1974 on Marriage, as amended by the Constitutional Court Decision Number 69/PUU-XIII/2015.